The Legal Framework in Management of Indonesian Special Economic Zones - Suparji Achmad (Varia Justicia, 2021)
The purpose this paper is to determine the legal aspects of special economic zones in the development of the national economy for the welfare of the people, increasing competitiveness for the national interest. In addition, this study uses a normative juridical method with a comparative approach and a descriptive qualitative approach. The results of this study indicate that economic management based on Free Trade Zones and Free Ports is not more profitable than the management of Special Economic Zones, because of that there are many views that various free trade legal products are too beneficial for foreign parties and detrimental to domestic interests.